2019
DOI: 10.1155/2019/5426974
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Identifying Biomarkers and High-Affinity Aptamers for Gynecologic Cancers Diagnosis and Therapy

Abstract: Cancer is the uncontrollable abnormal division of cell growth, caused due to the varied reasons. Cancer can be expressed in any part of the body, and it is one of the death-causing diseases. Human reproductive organs are commonly damaged by cancer. In particular, the women reproductive system is affected by various cancers including ovarian, cervical, endometrial, vaginal, fallopian tube, and vulvar cancers. Identifying these cancers at earlier stages prevents the damage to the organs. Aptamer is the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Although predictive values were missing in a number of studies included, sensitivity and specificity appeared to be similar across, and consistent with earlier review conducted by Jiang et al which recorded sensitivity, specificity, and AUC of 73, 94%, and 0.95, respectively, with 13.2 Positive Likelihood Ratio (PLR), and 0.28 Negative Likelihood Ratio (NLR) [ 53 ]. Experimental studies have shown that epigenetic instability is greatly influenced by miRNA which plays important role in transcriptional regulation, and any form of dysregulation as seen in overexpression often lead to a wide range of human malignancy including cervical cancer [ 2 , 3 , 11 ]. Like many other circulating miRNAs, studies have established that miR-9 could be useful for early detection of cervical cancer, predicting cancer prognosis, and in monitoring clinical outcome of cancer disease [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although predictive values were missing in a number of studies included, sensitivity and specificity appeared to be similar across, and consistent with earlier review conducted by Jiang et al which recorded sensitivity, specificity, and AUC of 73, 94%, and 0.95, respectively, with 13.2 Positive Likelihood Ratio (PLR), and 0.28 Negative Likelihood Ratio (NLR) [ 53 ]. Experimental studies have shown that epigenetic instability is greatly influenced by miRNA which plays important role in transcriptional regulation, and any form of dysregulation as seen in overexpression often lead to a wide range of human malignancy including cervical cancer [ 2 , 3 , 11 ]. Like many other circulating miRNAs, studies have established that miR-9 could be useful for early detection of cervical cancer, predicting cancer prognosis, and in monitoring clinical outcome of cancer disease [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer cases continue to rise despite concerted efforts to provide rapid and effective screening coupled with intensified human papilloma virus (HPV) vaccination to selected age category of females [ 1 ]. Currently, the global incidence and mortality estimate of cervical cancer have risen to 569,847 and 311,365 respectively, with cases in sub-Saharan countries such as Kenya reported at 5250 (12.9%) and 3286 (11.84%) annually respectively, majorly from infection with high risk human papilloma virus (HR-HPV)16/18 [ 1 ].. Cervical carcinogenesis is characterized majorly by 1) increased expression of E6 and E7 genes of high risk HPVs, known to bind to and inactivate p53 and pRb oncosuppressors; 2) integration of viral DNA into host genome, with disruption of E2 viral genes and host chromosomal loci; and 3) molecular alterations of key regulators of cell cycle; all of which can be examined to predict a possible neoplasia using suitable probes such as DNA, RNA, antibody, protein, and aptamers [ 2 , 3 ]. Today, great efforts have been made to identify novel biomarkers aiming to improve detection of the invasive cervical cancer at the earliest stage possible.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous high-throughput genomic and proteomic studies comparing healthy and cancerous cells have identified many such potential drug targets [9,12,13]. These putative targets are then subjected to high-throughput screening with libraries of potential drug candidates, such as peptides, antibodies, natural compounds, chemicals, and aptamers [10,[14][15][16][17][18][19][20][21][22]. Selected molecules that specifically bind to the target are considered for further functional validation [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Papanicolaou exam (Pap) is still the main method used to detect CC and its precursor lesions [17] and is a cytological screening test that detects abnormal epithelial cells scraped from the transformation zone of the cervix [18]. Several criteria exist to assess the degree of change, including the nucleus/cytoplasm ratio, nuclear shape and intensity of the nuclear marks and chromatin.…”
Section: Existing Tests For the Examination Of Cervical Lesion Pap Smmentioning
confidence: 99%
“…The main lines of research associated with these aspects focus mainly on the identification of cellular/tissue or circulating proteins whose expression is altered in response to the expression of viral oncoproteins; investigating changes in the methylation pattern of several cellular genes that could efficiently predict neoplastic initiation; changes in chromosomes and/or viral genome in different regions and recognised as modified by the viral integration event; the identification of polymorphisms associated with a better prognosis [18,23].…”
Section: Identification Of Biomarkers Associated With Hpv Expression mentioning
confidence: 99%